1979
DOI: 10.1063/1.325779
|View full text |Cite
|
Sign up to set email alerts
|

The dependence of the piezoelectric response of poly(vinylidene fluoride) on phase-I volume fraction

Abstract: Investigations of the dynamic piezoelectric response (d*31 and e*31) of unoriented poled poly(vinylidene fluoride) films containing different volume fractions of phase-I and phase-II crystalline materials show a linear relationship between phase-I content and piezoelectric response. Samples were poled under conditions (106 V/cm at 23 °C) which produced no observable changes in x-ray diffraction patterns taken before and after poling. The piezoelectric strain constant of the unoriented phase-II film is d′31=0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…It also appears that the onset of the plateau region for dp begins at ~l06 V/cm, a much lower value of Ep than for the onset of the plateau region for P . fields up to and including 2 x 106 V/cm are identical within experimental error, indicating that the poling mechanism is probably 180' switching of the molecular dipoles producing a 180' rotation of crystallites as previously suggested (2) . This would be consistent with the development of film polarization and the lack of change in the x-ray diffraction patterns.…”
Section: Resultssupporting
confidence: 58%
“…It also appears that the onset of the plateau region for dp begins at ~l06 V/cm, a much lower value of Ep than for the onset of the plateau region for P . fields up to and including 2 x 106 V/cm are identical within experimental error, indicating that the poling mechanism is probably 180' switching of the molecular dipoles producing a 180' rotation of crystallites as previously suggested (2) . This would be consistent with the development of film polarization and the lack of change in the x-ray diffraction patterns.…”
Section: Resultssupporting
confidence: 58%
“…39,40 Moreover, the piezoelectricity of the polarized PVDF film is enhanced with the increase of β phase content. 41,42 However, the stretch-induced α−β phase transformation is often incomplete, and the nonpolar α phase (about 20%) is always retained. 31,36,38 The high stretching ratio (>4) is needed to obtain the high content of the β phase; the stretched films with lattice defects and low crystallinity result in relatively low piezoelectric properties and poor thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…As reported, compared to unoriented films with mainly β phase, oriented β-films after stretching show enhanced dielectric properties. , During stretching, the c -axis of the molecular chains is preferentially oriented along the stretching direction. Because the electric field is perpendicular to the film surface, the molecular chains oriented parallel to the stretching direction strongly contribute to dipole alignment. , Moreover, the piezoelectricity of the polarized PVDF film is enhanced with the increase of β phase content. , However, the stretch-induced α–β phase transformation is often incomplete, and the nonpolar α phase (about 20%) is always retained. ,, The high stretching ratio (>4) is needed to obtain the high content of the β phase; the stretched films with lattice defects and low crystallinity result in relatively low piezoelectric properties and poor thermal stability. , …”
Section: Introductionmentioning
confidence: 99%
“…Although X-ray diffraction data of the doped films have suggested that some preferential positioning of the dopant at the crystallite boundaries may occur, with no evidence of diffusion of the dopant into the crystalline regions, additional studies are required to gain some understanding of the mechanisms involved. PVF2 is a semicrystalline polymer and its crystallinity is usually around 50% [2][3][4][5] (recently, perdeuteriated PVF2 films were found to have much higher crystallinity6). Since there was no indication (from X-ray diffraction studies) of the plasticizer diffusing into the crystalline regions,1 most of the plasticizer must be in solution outside the crystalline regions.…”
Section: Introductionmentioning
confidence: 99%